Mahathir Mohamad as a cultural relativist: Mahathirism on human rights - Mohd Sani, Mohd Azizuddin (2008)
This paper is about Mahathirism, or Mohamad Mahathir's views on human rights. It supports the argument that Mahathirism is in fact a type of cultural relativism, as opposed to universalism or Western liberalism, specifically in the Malaysian context. The main idea of Mahathirism comes from Mahathir's concept of 'Asian values'. His argument about Asian values can be split into the philosophies on anti-Western imperialism, strong government, communitarianism, and social and economic rights. Mahathir rejects universalism or the Western liberal notion of human rights, which, he believes, can corrupt Malaysian culture and religious beliefs. Mahathir claims that Western pressure on developing countries, including Malaysia, over human rights and democratisation is intended to cause instability, economic decline and poverty. With such a situation, the West can threaten and control Malaysia. However, critics dispute Mahathir's purported intention in restricting human rights, arguing that his real intention was to exploit these issues as a justification for curtailing opposition and reinforcing his position in power, as well as to hide human rights violations in Malaysia.